2015
DOI: 10.1021/acs.jpca.5b04435
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of 2(3H) and 2(5H) Furanones: Theoretical Aspects

Abstract: The thermal decomposition reactions of 2(3H) and 2(5H) furanones and their methyl derivatives are explored. Theoretical calculations of the barriers, reaction enthalpies, and the properties of these and intermediate species are reported using the composite model chemistry CBS-QB3 and also the functional M06-2X allied to the 6-311++G(d,p) basis set. Thus, the bond dissociation enthalpies, ionization energies, and unimolecular chemical kinetic rate constants in the high-pressure limit were computed. We show that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Examination of PIE­( m / z 84) at 1300 K when all m / z 83 is consumed does show that trace amounts of m / z 84 grow in between 9.5 and 10 eV, which could indicate the possibility of both 2­(3 H )-furanone (IE = 9.3–9.7 eV) and 2­(5 H )-furanone (IE = 10.2–10.65 eV). , The ionization energy of 2­(5 H )-furanone is likely lower than the reported value of 10.65 eV; samples of 2­(5 H )-furanone seeded in He were pulsed through an unheated reactor, and ions at m / z 84 were detected by 10.487 eV photoionization mass spectrometry. A more detailed discussion of these experiments is reported elsewhere; a quantum chemical study of the thermochemistry and kinetics of these lactones is also presented in works by Würmel and Simmie. , …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Examination of PIE­( m / z 84) at 1300 K when all m / z 83 is consumed does show that trace amounts of m / z 84 grow in between 9.5 and 10 eV, which could indicate the possibility of both 2­(3 H )-furanone (IE = 9.3–9.7 eV) and 2­(5 H )-furanone (IE = 10.2–10.65 eV). , The ionization energy of 2­(5 H )-furanone is likely lower than the reported value of 10.65 eV; samples of 2­(5 H )-furanone seeded in He were pulsed through an unheated reactor, and ions at m / z 84 were detected by 10.487 eV photoionization mass spectrometry. A more detailed discussion of these experiments is reported elsewhere; a quantum chemical study of the thermochemistry and kinetics of these lactones is also presented in works by Würmel and Simmie. , …”
Section: Resultsmentioning
confidence: 99%
“…Recent electronic structure calculations indicate that the lowest-energy decomposition route of 5-methyl-2­(5 H )-furanone is ring opening to 1-pentene-1,4-dione, as shown in Scheme 4.5 . The furanone could also decompose through an addition–elimination reaction with H atom, converting the 2­(5 H ) intermediate to 5-methyl-2­(3 H )-furanone (α-angelica lactone), which has been shown to eliminate CO and produce MVK either through a concerted reaction , or through an open-chain pentene-dione intermediate . A similar addition–elimination reaction was suggested to be a favorable route to interconvert the unmethylated furanones, 2­(3 H )- and 2­(5 H )-furanone.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that pathway I was relatively more frequently observed than pathway II. However, pathway II is a reaction pathway experimentally observed by Xu et al 8 and calculated by Wuermel et al, 9 employing a theoretical approach. In addition, CO 2 is not the main product of 2-furanone pyrolyzing; instead, the reaction will give CO and propenal as the products.…”
Section: Energy and Fuelsmentioning
confidence: 99%
“…Understanding the reaction pathways of bio-oil combustion is important for better use of bio-oil, but limited research has been reported in that regard. Oxidation or pyrolysis reaction pathways of furan- and phenol-derived compounds, such as furanone, , phenol, cresol, catechol, , hydroquinone, and dimethoxybenzene, have been largely investigated. Although the structure of these compounds is very similar to those contained in bio-oil, reactivity of furan- or phenol-derived compounds may vary during the combustion of bio-oil samples.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation